1999
DOI: 10.1523/jneurosci.19-14-06145.1999
|View full text |Cite
|
Sign up to set email alerts
|

Neural Correlates of Perceived Brightness in the Retina, Lateral Geniculate Nucleus, and Striate Cortex

Abstract: Brightness changes can be induced in a static gray field by modulating the luminance of surrounding areas. We used this induction phenomenon to investigate the neural representation of perceived brightness. Extracellular recordings were made in striate cortex, the lateral geniculate nucleus (LGN), and the optic tract of anesthetized cats using stimuli that produced brightness induction. While a cell's receptive field (RF) was covered by uniform gray illumination, the luminance of rectangular flanking regions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
147
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(172 citation statements)
references
References 35 publications
22
147
3
Order By: Relevance
“…Neurophysiological studies in monkey suggest that a subpopulation of V1 and V2 neurons respond to luminance modulations well outside their classical receptive field (Kinoshita and Komatsu, 2001;Roe et al, 2005), in a manner qualitatively consistent with brightness perception. Similar results have been reported in cats (Rossi et al, 1996;Rossi and Paradiso, 1999;Hung et al, 2001). Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys.…”
Section: Comparison To Neurophysiological Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Neurophysiological studies in monkey suggest that a subpopulation of V1 and V2 neurons respond to luminance modulations well outside their classical receptive field (Kinoshita and Komatsu, 2001;Roe et al, 2005), in a manner qualitatively consistent with brightness perception. Similar results have been reported in cats (Rossi et al, 1996;Rossi and Paradiso, 1999;Hung et al, 2001). Friedman et al (2003), however, found no evidence for color filling-in signals in V1 and V2 of awake behaving monkeys.…”
Section: Comparison To Neurophysiological Resultssupporting
confidence: 85%
“…Recent modeling work suggests that the majority of V1 responses reported by Kinoshita and Komatsu (2001) can be understood on the basis of local and mean luminance processing and that only a small minority of responses are consistent with edge-driven surface activity, such as brightness filling-in (Vladusich et al, 2006). We speculate that the properties of these previously determined surface-responsive neurons (Rossi et al, 1996;MacEvoy et al, 1998;Rossi and Paradiso, 1999;Hung et al, 2001;Kinoshita and Komatsu, 2001;Roe et al, 2005) may in fact arise from the mechanisms underlying the extended edge responses we observed in our study, and so are presumably not directly related to our perception of brightness, color, or filling-in.…”
Section: Comparison To Neurophysiological Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…Our result also can account for neurophysiological results from the cat, which show that most V1 and some lateral geniculate nucleus neurons modulate their firing rate in correlation with the perceived brightness of achromatic stimuli within their receptive field (17)(18)(19); the influence of the surround on the responses of these cells is not attributable to feedback from higher areas, as postulated, but is a consequence of the fact that relative brightness is calculated at the monocular level.…”
Section: Discussionsupporting
confidence: 75%
“…For instance, in brightness induction [56], the perceived brightness of a static gray field changes as the luminance of the surrounding areas is modulated, a change that is not reflected in the responses of ganglion cells [57]. Brightness perception likely involves interactions on a larger spatial scale than those observed in the retina [58].…”
Section: Peripheral Code Of Perceived Intensity In Other Sensory Modamentioning
confidence: 99%